The Influence of Fear on Risk Taking: A Meta-Analysis - Wake, Sean (Cogn Emot, 2020)
A common finding in the study of emotion and decision making is the tendency for fear and anxiety to decrease risk taking. The current meta-analysis summarizes the strength and variability of this effect in the extant empirical literature. Our analysis of 136 effect sizes, derived from 68 independent samples and 9,544 participants, included studies that experimentally manipulated fear or measured naturally varying levels of fear or anxiety in both clinical and non-clinical samples, and studies measuring risky decision-making and risk estimation. A multilevel random effects model estimated a small to moderate average effect size (r = 0.22), such that fear was related to decreased risky decision making and increased risk estimation. There was also high heterogeneity in the effect sizes. Moderator analyses showed that effect sizes were greater when risk tasks that used tangible (e.g. monetary) outcomes, and when studies used clinically anxious participants. However, there also remained considerable variability in effect sizes the sources of which remain unknown. We posit several potential factors that may contribute to observed variability in this effect for future study, including factors concerning both the nature of fear experience and the risk taking context.